2012
DOI: 10.1002/app.37580
|View full text |Cite
|
Sign up to set email alerts
|

Copolymer‐induced silk‐based hydrogel with porous and nanofibrous structure

Abstract: A novel physical blend method was developed to accelerate the self-assembly process of silk fibroin (SF) solution into porous and nanofibrous hydrogel by temperature-sensitive copolymer. Silk-based hydrogel was firstly achieved through blending SF solution with copolymer aqueous solution and then removed the copolymer from blend solution by heat treatment (50 C) after 24 h hydrogelation. Copolymer molecules would interact with SF molecules resulting in reduction of copolymer micelles, which further affect the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Recent studies revealed that the slow dynamics of gelation for a pure SF solution is mainly relevant with conformational transition from random coil to β-sheet structure, which then gradually self-assembles into close-packed β-sheet crystals, acting as a physical cross-link to stabilize SF hydrogel. ,, Although many physical treatment methods (e.g., pH, vortexing, sonication, and electrical field), or the addition of certain organic molecules (e.g., ethanol, surfactants, or hydrophilic polymers), are able to increase the gelation rate of SF by adjusting protein chain–chain interactions, the gelation process induced by instrumental parameters may not be compatible with certain clinical environments, and potential toxicity of certain organic molecules can raise a significant concern for biomedical applications. Thus, searching for a simple and biocompatible way to trigger the gelation of SF is highly desirable.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies revealed that the slow dynamics of gelation for a pure SF solution is mainly relevant with conformational transition from random coil to β-sheet structure, which then gradually self-assembles into close-packed β-sheet crystals, acting as a physical cross-link to stabilize SF hydrogel. ,, Although many physical treatment methods (e.g., pH, vortexing, sonication, and electrical field), or the addition of certain organic molecules (e.g., ethanol, surfactants, or hydrophilic polymers), are able to increase the gelation rate of SF by adjusting protein chain–chain interactions, the gelation process induced by instrumental parameters may not be compatible with certain clinical environments, and potential toxicity of certain organic molecules can raise a significant concern for biomedical applications. Thus, searching for a simple and biocompatible way to trigger the gelation of SF is highly desirable.…”
Section: Introductionmentioning
confidence: 99%
“…SF scaffolds have been prepared in various methods, e.g., freeze‐drying, salt leaching, gas foaming, electrospinning, and nonwoven techniques . Based on the above methods, SF scaffolds can be fabricated into various forms, including film, hydrogels, nonwoven fabrics, and 3D porous scaffolds . However, SF does not have antimicrobial properties, which often result in wound infection.…”
Section: Introductionmentioning
confidence: 99%
“…However, the clinical appli-cation of silk fibroin is limited because of its time consuming nature; it often takes too long to form a hydrogel unless nonphysiological treatments are used (e.g., low pH and high temperature) 8 . In an attempt to combat this disadvantage, some studies have reportedly added polyethylene oxide (PEO) and polymeric surfactants to accelerate the hydrogelation, but they only shortened the hydrogelation time for a limited range 9 . Furthermore, Wu et al 10 found that adding sodium dodecyl sulphate (SDS) as the gelling agent under mild conditions (37 ºC and pH 7.0 ± 0.2) could reduce the silk fibroin gelation time.…”
Section: Introductionmentioning
confidence: 99%